2022
DOI: 10.1055/s-0042-1742333
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Administrative Databases and Big Data on Understanding Glioma Treatment—A Systematic Review

Abstract: Background Gliomas are a heterogeneous group of tumors where large multicenter clinical and genetic studies have become increasingly popular in their understanding. We reviewed and analyzed the findings from large databases in gliomas, seeking to understand clinically relevant information. Methods A systematic review was performed for gliomas studied using large administrative databases up to January 2020 (e.g., National Inpatient Sample [NIS], National Surgical Quality Improvement Program [NSQIP], a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 129 publications
(290 reference statements)
0
3
0
Order By: Relevance
“…The fact that XRCC7 gene polymorphism was also present in a significant number in control group points to the multifactorial etiology of the disease. Furthermore, some studies have found that human chromosome number 8q11 (which also contains the XRCC7 gene) can functionally correct the hyper-radiosensitivity of severe combined immunodeficiency cells, which are otherwise extremely prone to radiation induced DNA damage, [5][6][7] helping guide the treatment for different types of gliomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that XRCC7 gene polymorphism was also present in a significant number in control group points to the multifactorial etiology of the disease. Furthermore, some studies have found that human chromosome number 8q11 (which also contains the XRCC7 gene) can functionally correct the hyper-radiosensitivity of severe combined immunodeficiency cells, which are otherwise extremely prone to radiation induced DNA damage, [5][6][7] helping guide the treatment for different types of gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…L27425) being the antisense primer. 5 The primers amplified 368-bp fragment containing the G/T variant in intron 8, which were then subjected to digestion with PvuII (New England BioLabs, Inc., Beverly, Massachusetts, United States) at 37°C overnight. The homologous GG allele had only one band of 368-bp; the heterozygous allele (GT) had three bands of 368, 274, and 94 bp; and the homozygous TT allele had two bands of 274 and 94 bp because of the gain of the restriction site.…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, the latter type of datasets has been used in various fields to analyze actual data and obtain valuable knowledge to handle particular situations. In the medical and health-care field, clinical-administrative datasets would allow for capitalization, management and retrieval of relevant information [17].…”
Section: Introductionmentioning
confidence: 99%